Flexible Integration Methods of Association of Southeast Asian Nations in the Formation of Legal Framework on the Science, Technology and Innovation - M. L. Entin; A. A. Vadov (Московский журнал международного права, 2025)
INTRODUCTION. Southeast Asia possesses substantial resources and a favorable geographical position, enabling participation in global value chains, which provides a significant impetus for the region’s technological development. However, ASEAN member states face challenges such as brain drain, delays in technology commercialization due to underdeveloped patent systems, and cultural-legal gaps. For these reasons, this study investigates ASEAN’s flexible integration methods to ensure the free movement of researchers and innovations, develop the patent system, and improve mechanisms for funding science, technology, and innovation.MATERIALS AND METHODS. The research is based on ASEAN agreements, legal acts, strategic and official documents related to the legal regulation of science, technology, and innovation. Additionally, international agreements in the field of patent law and legally significant indicators from the WIPO database were analyzed. The study also considers publications by Russian and international scholars (primarily ASEAN nationals) in international and integration law. General scientific and specialized legal methods, including legal positivist, systemic-legal, comparativelegal, and historical-legal methods, were used.RESEARCH RESULTS. The evolution of ASEAN’s legal acts in the regulation of science, technology, and innovation demonstrates that the region avoids directly replicating EU models. Instead, it combines the gradual implementation of measures to ensure the free movement of researchers and technology exchange, adapted to the national specificities of member states. The flexibility of integration measures is also confirmed by the member countries’ right to opt out of specific joint initiatives.DISCUSSION AND CONCLUSIONS. Since 1997, ASEAN has encountered cultural and legal gaps among member states in forming unified legislation in science, technology, and innovation. As a result, in 2010, a decision was made to focus on the economic foundation of technological development rather than the socio-cultural aspects. Consequently, in 2012, ASEAN agreement on the movement of natural persons was signed, and measures for the mutual recognition of qualifications were introduced. National patent systems were harmonized with international standards, which accelerated the registration of technological patents within ASEAN. While it also led to an increase in patents filed by foreign entities. A solution emerged through the establishment of a specialized body – the ASEAN IP Academy. Academy proposes improvements to national patent systems and trains scientific and technological personnel to file patents under the new rules. Thus, Southeast Asian countries, striving to develop their own technological markets, employ ASEAN’s flexible integration methods to balance embedding their economies into global technological value chains with fostering their own innovation potential based on mediumand high-level technologies from global leaders.